Про зміни викладання іншомовної культури в українських вузах - Нічий, Валентина Володимирівна (Актуальні питання суспільних наук та історії медицини: Спільний українсько-румунський науковий журнал, 2022)
The purpose of the article is to analyze the features of teaching foreign languages in Ukrainian universities. To achieve this goal, the article uses the methods of critical analysis of scientific resources and scientific observation of the educational process, theoretical analysis. A comprehensive description of the application of these methods through the prism of foreign languages is the scientific novelty of the work. The main purpose of learning a foreign language in modern conditions is to form students' ability to communicate in any language at any level, which allows them to enter into equal dialogue with other cultures and traditions, participate in various spheres of intercultural communication, join modern world civilization. This goal involves the development of students with a high level of communicative competence, which will allow, in accordance with their real needs and interests, to successfully and efficiently carry out speech communication in various fields. The method of learning a foreign language is a system of knowledge about the natural processes of its study and ways to influence this process in order to optimize it. There are two functionally different techniques: general and specific. The general technique is devoted to the study of the features and patterns of the process of learning a foreign language, regardless of the language in question. For example, the principles of selection of educational material, the correlation of oral and written language at different stages of the lesson will be the same in equivalent learning conditions for any Western European language. Conclusions. Today, more and more teachers use elements of a communicative-oriented approach in foreign language lessons. As a result of this approach in teaching, a system of foreign language proficiency is formed, implemented and operates as a means of communication in the broadest sense of the word. This approach also includes the development of skills to compare the linguistic phenomena of the native and foreign languages. With the help of a communication-oriented approach, all aspects of a foreign language can be taught. When learning to speak a foreign language, the principle of individual approach becomes very important. Learning a foreign language, perhaps more than any other subject, requires an individual approach. The individual approach should not be considered as a one-time tool, which is usually used at one stage of mastering the material and in relation to any one group of students; it must permeate the whole process of learning to speak a foreign language.
Keywords: foreign languages, communication-oriented approach, foreign language culture, educational process